Tourism in an Era of Uncertainty Rhodes Island, Greece 27–30 April 2011 - Andriotis, Konstantinos; Theocharous, Antonis L.; Kotsi, Filareti; Zopiatis, Anastasios (My University, 2011)
The twenty-first century has brought new challenges for tourism. Climate change, infectious diseases, economic crises, terrorism, globalisation, and entrenched social problems pose threats and create an uncertain tourism environment that affects destinations and their populations in virtually every corner of the contemporary world. To keep pace with these challenges, governments, businesses, communities, and tourism organisations need to continuously assess environmental factors, to identify future trends and to examine various response policies and management techniques to decrease risk and uncertainty. Bearing all these in mind, ICOT 2011 aims to contribute to the debate on tourism in relation to different aspects of uncertainty, by stimulating discussion and exchange of ideas between tourism professionals, academics, researchers, policy-makers, consultants, practitioners, government officials and postgraduate students from tourismrelated fields.
Keywords: tourism; Ecotourism